Active systems in the vibration control of heavy machine driver’s seats - BALLO, I.; SZUTTOR, N. (Archives of Acoustics, 1985)
The paper deals with vibration damping properties of passive vibration control means used in driver’s seats of heavy earth moving machines. The significant improvement of vibration control reached by an active vibration control system of an electrohydraulic type is described. The advantages and perspectives of electropneumatic active vibration control systems for driver’s seats is stressed.